Peningkatan Kemampuan Orang Tua dan Kader Posyandu dalam Menangani Anak Tunagrahita melalui Pelatihan di Kelurahan Klojen Malang - Maria Vianti Desa; Sri Wahyuni; Klemensia Nini; Yunita Kono Abi (Jurnal Surya Masyarakat, 2025)
The program was carried out in response to complaints from a number of parents in Klojen Village, Malang City who experienced difficulties in assisting children with intellectual disabilities, especially in mastering basic skills such as reading and arithmetic. Although Posyandu activities and routine therapy for people with disabilities have been running every month, parents and Posyandu cadres still experience obstacles in providing optimal treatment to children with intellectual disabilities. This training program aims to improve the understanding and skills of parents and Posyandu cadres in providing appropriate assistance to children with intellectual disabilities. The implementation of the activity uses a participatory approach that includes preparation, problem identification, planning, implementation, and evaluation. The training was given to 21 participants consisting of parents and Posyandu cadres who participated in this training. The evaluation results showed a significant increase in participants' knowledge and skills, from an average pre-test score of 34% to 85.57% in the post-test with a difference of 49.33%. These results demonstrate the effectiveness of the training in improving participants' competencies, particularly in understanding the material and developing reading and arithmetic skills to better support children with intellectual disabilities. The program also successfully fostered networking among parents, integrated health post (Posyandu) cadres, and other stakeholders who play an active role in supporting children's sustainable growth and development. The success of this training emphasizes the importance of community empowerment as an alternative solution to the limitations of professional services and has the potential to be implemented in other areas to strengthen inclusive support for children with intellectual disabilities.